FESTIVAL EXPERIENCES AND URBAN TOURISM: INSIGHTS FROM VISITORS’ PERCEPTIONS OF MAJOR CULTURAL EVENTS IN ORADEA, ROMANIA - Bâc, Dorin; Chira, Alexandru; Simut, Ramona; Chi?, Alexandru Ionu?; Ecer, Zeynep Ceylin; Wendyfrawv, Endalamaw Kindie (Editura Universitatii din Oradea, 2025)
This study analyzes visitors’ perceptions of three major cultural events in Oradea—the Easter Fair, the Medieval Festival, and the Christmas Fair. The objective compares visitors’ perceptions of three cultural events in Oradea to assess whether statistically significant differences exist across key dimensions of the festival experience. Data was collected through 325 structured questionnaires administered on-site at the three events. Visitors’ evaluations were analyzed using Chi-square tests to assess categorical differences, Kruskal–Wallis tests for ordinal distributions, and Welch’s t-tests/ANOVA for subgroup comparisons by age and residency. The analysis indicates the varying strengths between the three events in Oradea. The Christmas Fair achieved the highest ratings in gastronomy and attracted a wide audience from different age groups, mainly due to its festive atmosphere. In contrast, the Medieval Festival was particularly appreciated for its artistic content, especially among older participants. Furthermore, the results show that both the Christmas and Medieval Festivals consistently outperform the Easter Fair in terms of atmosphere, authenticity related to local and handmade products, and organizational elements such as cleanliness and safety. Subgroup analyses show that younger visitors place greater emphasis on atmosphere, while older participants prioritize safety. Local residents tend to be more critical of organizational aspects. In particular, the Easter Fair seems to be the most inconsistent, presenting significant differences within the same group in terms of food offerings, atmosphere, safety, information, and facilities. Overall, these results highlight the fact that each festival offers a unique experience that attracts different audiences. The Easter Fair requires strategic improvements to enhance authenticity and organizational clarity, while the Christmas Fair and Medieval Festival demonstrate greater coherence but still demand target adjustments. © 2025, Editura Universitatii din Oradea. All rights reserved.
Keywords: cultural festivals; event tourism; Oradea; urban tourism; visitors’ perceptions